ANTHELMINTIC ACTIVITY TEST OF BIDARA ARAB LEAVES ETHANOL EXTRACT (Ziziphus spina-christi (L.) Desf.) AGAINST PORK ROUND WORMS AND THEIR EGGS (Ascaris suum Goeze) IN VITRO - Mufliha Dzan Nuroyni; Sri Peni Fitrianingsih; Ratu Choesrina (UNISBA Press, 2023)
Worm infection is one of the most common diseases in developing countries such as Indonesia. Indonesia is a country with a very high level of biodiversity, including the diversity of medicinal plants. Bidara Arab (Ziziphus spina-christi) is one of the medicinal plants that can be used as an anthelmintic. This study aims to scientifically prove the anthelmintic activity of ethanol extract of bidara arab leaves against pig roundworm and their eggs (Ascaris suum Goeze) in vitro. The test was divided inti 3 groups, the test group (20%, 25%, and 30% concentration), the comparison group (Pirantel Pamoat 0,2% and Piperazin Sitrat 15% for pork round worms, and Albendazol 0,15% for helminth eggs), and negative control group (Hank Salin and CMC-Na 0,5%). The parameters observed were the type of paralysis, time, percentage of paralysis and death in worms, and the percentage inhibition of fertile egg development in worm eggs. The results showed that the 20%, 25% and 30% concentrations of bidara arab leaves extract had anthelmintic activity and caused flasid paralysis in adult pork round worms and had ovicidal effect on worm eggs. The best and most potent activity was shown at 30% concentration